Intracortical myelin in individuals with alcohol use disorder: An initial proof‐of‐concept study. Issue 10 (14th September 2022) - Morris, Vanessa; Bock, Nicholas; Minuzzi, Luciano; MacKillop, James; Amlung, Michael
Abstract: Introduction: Disruption of cortical gray matter and white matter tracts are well‐established markers of alcohol use disorder (AUD), but less is known about whether similar differences are present in intracortical myelin (ICM, i.e., highly myelinated gray matter in deeper cortical layers). The goal of this study was to provide initial proof‐of‐concept for using an optimized structural magnetic resonance imaging (MRI) sequence to detect differences in ICM in individuals with AUD compared to control participants reporting drinking within recommended guidelines. Methods: This study used an optimized 3T MRI sequence for high intracortical contrast to examine ICM‐related MRI signal in 30 individuals with AUD and 33 healthy social drinkers. Surface‐based analytic techniques were used to quantify ICM‐related MRI signal in 20 bilateral a priori regions of interest based on prior cortical thickness studies, and exploratory vertex‐wise analyses were examined using Cohen's d effect size. Results: The global distribution of ICM‐related signal was largely comparable between groups. Region of interest analysis indicated that AUD group exhibited greater ICM‐related MRI signal in precuneus, ventromedial prefrontal cortex, posterior cingulate, middle anterior cingulate, middle/posterior insula, and dorsolateral prefrontal cortex (Cohen's d s = 0.50–0.75). Four regions (right precuneus, ventromedial prefrontal cortex, posterior cingulate and left dorsolateral prefrontal cortex) remained significant ( p < .05) after covarying for smoking status. Conclusion: These findings provide initial evidence of ICM differences in a moderately sized sample of individuals with AUD compared to controls, although the inflation of type 1 error rate necessitates caution in drawing conclusions. Robustly establishing these differences in larger samples is necessary. The cross‐sectional design cannot address whether the observed differences predate AUD or are consequences of heavy alcohol consumption. Abstract : This study provides initial proof‐of‐concept for an optimized structural magnetic resonance imaging sequence to detect differences in intracortical myelin (ICM) in people with alcohol use disorder compared to social drinkers. Surface‐based analytic techniques were used to quantify ICM in 20 regions of interest and across the entire cortex. The global distribution of ICM was largely comparable between groups, although the alcohol use disorder group exhibited greater ICM signal in regions of precuneus, prefrontal cortex, posterior cingulate, anterior cingulate, and insula.